Opening doors to life: A suicidal behavior prevention program involving Gatekeeper teachers - Solarte, María Camila; Araujo, Omaira Lucely; Muñoz, Diego Fernando; Villalobos, Fredy Hernán; Ceballos, Ana Karen; Luna, Edwin Gerardo (Universidad y Salud, 2024)
Introduction: Suicide is the third cause of death in young people aged between 15 to 19 years. Thus, school environments can promote mental health of adolescents through early identification of risk factors and prevention of suicidal behaviors. One prevention strategy is the training of “gatekeepers”. Objective: To determine the impact of the “Opening Doors to Life” program on the knowledge, attitudes, and practices regarding prevention of suicidal behavior in a set of high school teachers from an educational institution in San Juan de Pasto, Colombia. Materials and methods: A pre-experimental study with an intervention group and pre- and post-follow-up measurements. Nine volunteer teachers participated during two training sessions. Results: Positive changes regarding knowledge, attitudes, and practices of the participants during pretest and posttest were observed for the majority of evaluated sub-dimensions. However, after three years, the positive measures prevailed only for knowledge about suicidal behavior and attitudes toward prevention. Conclusion: The “Opening Doors to Life” program showed effectiveness and relevance. However, maintaining its impact requires follow-up actions and support of trained teachers.